Challenges, Opportunities, and Future Research in the Integration of 5G/6G Networks, LEO Satellites, and IoT for Environmental Protection and Sustainable Development at ECSTAR - Settapong Malisuwan (Journal of Environmental Science and Engineering B, 2023)
The rapid proliferation of connected IoT (Internet of Things) devices, along with the increasing demand for 5G mobile networks and ubiquitous high-speed connectivity, poses significant challenges in the telecommunications sector.To address these challenges, a comprehensive understanding of the integration of 5G/6G networks and LEO (Low Earth Orbit) satellite networks is required, forming the concept of "integrated networks".Integration offers valuable advantages, including service continuity, wide-area coverage, and support for critical communications and emerging applications.This paper provides a high-level overview of the convergence of 5G/6G, LEO satellites, and IoT devices, shedding light on the technological challenges and standardization issues associated with the transition from 5G to 6G networks using NTNs (Non-Terrestrial Networks) based on LEO satellites.Furthermore, this research delves into the emerging social issues, potential possibilities, and the paradigm shift from the IoT to the IoI (Internet of Intelligence), which is poised to revolutionize the landscape of 6G wireless networks.By highlighting the interconnectedness of 5G/6G networks, LEO satellite systems, and IoT devices, it underscores the importance of leveraging these converging technologies to address environmental protection and achieve the United Nations SDGs (Sustainable Development Goals).In addition to providing valuable insights for readers seeking to comprehend the convergence of 5G/6G networks, LEO satellite systems, and IoT devices, this paper represents the outcomes of a comprehensive analysis conducted at the ECSTAR (Excellence Center of Space Technology and Research).Through an examination of technological challenges and advancements, it identifies future research directions and potential avenues for exploration at ECSTAR, thereby contributing to a broader understanding of integrated networks and their profound impact on future telecommunications systems.This research serves as a significant resource for advancing the knowledge and discourse surrounding the linkages between the convergence of these technologies, environmental protection, and the pursuit of the SDGs.
Keywords: IoT and Edge/Fog Computing; Satellite Communication Systems